OP0194 CD21-/LO Marginal Zone-Like B Cells in HCV-Related Mixed Cryoglobulinemia Vasculitis Highly Express FCRL5 Protein and are Specifically Killed by Anti-FCRL5 Immunotoxins. (23rd January 2014) - Terrier, B.; Nagata, S.; Ise, T.; Rosenzwajg, M.; Klatzmann, D.; Saadoun, D.; Cacoub, P.
Abstract : Background: Hepatitis C virus (HCV) is associated with B-cell lymphoproliferative disorders including mixed cryoglobulinemia (MC) and non-Hodgkin lymphoma. Fc receptor-like (FCRL) proteins comprise a newly identified family of immunoregulatory proteins with sequence similarity as Fc receptors. The transmembrane FCRL1-5 molecules are preferentially expressed on B lineage cells. Objectives: To analyze the expression of FCRL1-5 proteins on B cells and test the cytotoxicity of specific immunotoxins on clonal B cells. Methods: We analyzed by flow cytometry the expression of FCRL1-5 on B cells from 15 HCV-infected patients with type II MC, 20 HCV patients without MC and 20 healthy donors. Results: We found a markedly increased expression of FCRL5 and decreased expression of FCRL1 on clonal CD21 -/lo marginal zone-like B cells compared to other B cell subsets from the HCV patients and healthy donors. To evaluate FCRL5 as an immunotherapy target for HCV-related lymphoproliferation, we produced two anti-FCRL5 recombinant immunotoxins (F56-IT and F25-IT) based on anti-FCRL5 monoclonal antibodies and Pseudomonas exotoxin. The immunotoxins showed specific cytotoxicity against FCRL5-expressing clonal CD21 -/lo marginal zone-like B cells isolated from HCV patients as well as FCRL5-transfected cell lines. In contrast, no cytotoxicity was observed against T cells or conventional B cells. Conclusions: Taken together, our findings suggest that FCRL5-targeting therapies could be a specific treatment of HCV-related lymphoproliferation and other FCRL5-positive malignancies and/or autoimmune B-cell disorders. Disclosure of Interest: None Declared